Juvenile depression treatment with antidepressants from the selective serotonin reuptake inhibitors group (Bangladesh Journal of Medical Science, 2019)
Objective. The article presents the juvenile depression treatment effectiveness with antidepressants of the selective serotonin reuptake inhibitors group (SSRIs).Materials and methods.182 patients were examined, including 114 men (62.6%) and 68 women (37.4%), age range 16 to 25 years, on treatment in a psycho-neurological dispensary in the city of Korolev (Russia, Moscow region) from 2014 to 2018.Results and Discussion.Main characteristics comparison of SSRIs antidepressants therapeutic effect in young men and adults of mature age revealed statistically significant age differences concerning the onset rate and these drugs antidepressant effect characteristics, as well as the adverse events nature.Conclusion. The SSRIs antidepressants clinical action regularities for depression treatment in adolescence, their therapeutic effect features and dynamics allow us to state adequate indications for the these drugs administration in adolescence, considering their age specificity.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.615-623